Governing Change and Adaptation at Pacific Rim National Park Reserve (Canada) and Saadani National Park (Tanzania) - Orozco-Quintero, Alejandra (2016)
Graduate aleja@uvic.ca In what can be characterized as a period of rapid ecological change, the global community has now reached an agreement on the importance of protecting what remains of the world’s biological diversity. In 2011, world governments pledged to extend protected areas (PAs) to 17% of the earth’s surface. Although, accumulated research documents the role PAs areas play in coping with environmental change, much of conservation practice remains at odds with the actual purpose of conservation: to enable natural and human systems to adapt and sustain life. Challenges in PA planning and management, and their connections (or lack thereof) to wider socio-economic and institutional frameworks have made environmental governance a leading concern in the study of PAs. This research examined the nature and dimensions of environmental governance affecting adaptive capacity and the sustainability of protected landscapes, particularly for PAs deemed to have been established and/or operating through ‘participatory’ governance. These issues are explored through comparative research based on case studies of two coastal PAs: Pacific Rim National Park Reserve in Canada, and Saadani National Park in Tanzania. Methods utilized included gathering qualitative and spatial data through interactions with decision-making bodies and representatives of agencies at the village/First Nations and park levels, interviews with state authorities at district and higher levels and document research. The research findings on the two PAs and adjacent communities unravel the nature and dynamics of steering institutions, institutional interplay and spatial interconnectedness as they relate to cooperation, agency and adaptability within and around protected landscapes. An examination of spatial and institutional arrangements within national frameworks, and an examination of governance and management practice at the level of individual parks reveal significant mismatches between policy discourses on multi-level cooperation and actual ...